The Impact of the Guidance Technique of Stopping Negative Thinking on reducing Psychological Reluctance in Swimming Lessons among Female Students of Physical Education and Sports Science - tiba zaid; Ali Khalif (التربية الرياضية)
The significance of the current research lies in studying the impact of the Guidance Technique (Stopping Negative Thinking) to reduce psychological reluctance in swimming lessons among female students of Physical Education and Sports Sciences highlighting the concept of psychological reluctance and how to confront it in the swimming lessons. The research provides a comprehensive and integrated theoretical framework that benefits the guiding process, contributing to the development of guiding programs that help reduce or eliminate psychological reluctance. Additionally, this research offers a psychological reluctance scale, aiding in the evaluation and diagnosis of students for the purpose of guiding them. The research addressed an important segment represented by female students of the College of Physical Education and Sports Sciences, so the aim of the current research is to identify the impact of the guidance program according to the method (stopping negative thinking) to reduce psychological reluctance in the swimming lesson among female students of Physical Education and Sports Sciences, and achieving the research goal required the construction of two tools, namely: Firstly, a psychological reluctance scale in swimming lessons for female students of Physical Education and Sports Sciences. Secondly, a guiding program using the (Stopping Negative Thinking) method, consisting of 12 guiding sessions for female students of the College of Physical Education and Sports Sciences at the University of Baghdad, who exhibited high scores on the psychological reluctance scale in swimming lessons.